Annual performance analysis and optimization of a solar tower aided coal-fired power plant - Li, Chao; Zhai, Rongrong; Yang, Yongping; Patchigolla, Kumar; Oakey, John E.; Turner, Peter J. (Elsevier, 2019)
The integration of solar energy into coal-fired power plants has been proven as a potential approach in the utilization of solar energy to reduce coal consumption. Moreover, solar augmentation offers low cost and low risk alternatives to stand-alone solar thermal power plants. In this study, the annual performance of a solar tower aided coal-fired power (STACP) system is investigated, and the influence of thermal storage system capacity on the annual solar generating power and annual solar-to-electricity efficiency is explored. The thermal storage system capacity is optimized to obtain the lowest levelized cost of electricity (LCOE). At the same time, the influence and sensitivity of several important economic factors are explored and assessed. Results demonstrate that compared to a coal-fired power system, the reduction in the annual average coal consumption rate of the STACP system with high direct normal irradiance (DNI), medium DNI, and low DNI are 5.79, 4.52, and 3.22 g/kWh, respectively. At a minimum, the annual coal consumption can be reduced by 14,000 t in a 600 MWe power generation unit. Because the same solar field is considered under different DNI conditions, the LCOE in the high DNI, medium DNI, and low DNI scenarios are all fairly similar (6.37, 6.40, and 6.41 ¢/kWh, respectively). When the solar multiple is 3.0, the optimal thermal storage capacity of the STACP system, with high, medium, and low DNIs are 6.73, 4.42, and 2.21 h, respectively. The sensitivity analysis shows that the change in economic parameters exerts more influence on the STACP system with the high DNI compared with the other two scenarios.
Keywords: Annual performance; Solar tower aided coal-fired power plant; Solar multiple; Thermal energy storage capacity; Optimization